2013
DOI: 10.20965/jaciii.2013.p0433
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Effects of a Synchronously Reliant Agent on Human Beings

Abstract: The ability of human symbiosis robots to communicate is indispensable for their coexistence with humans, so studies on the interaction between humans and robots are important. In this paper, we propose amodel robot self-sufficiency system that empathizes with human emotions, a model in which we apply the urge system to an autonomous system of emotions. We carry out simulation experiments on this model and verify the psychological interaction between the software robot and its users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Second, the robot expressed autonomous emotions. Previous studies have indicated that a sympathetic agent enhances learning motivation [8] and that an agent using a model of emotional expressions facilitates more effective interactions with humans than the one expressing random emotions [5]. A similar effect was observed during collaborative learning between a learner and the robot.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Second, the robot expressed autonomous emotions. Previous studies have indicated that a sympathetic agent enhances learning motivation [8] and that an agent using a model of emotional expressions facilitates more effective interactions with humans than the one expressing random emotions [5]. A similar effect was observed during collaborative learning between a learner and the robot.…”
Section: Discussionmentioning
confidence: 63%
“…3), which has previously facilitated human-robot interactions. Moreover, this earlier report suggests that the agent, which uses Russell's circumplex model of affect, can prompt more effective interactions with humans than an agent using a conventional model [5]. In addition to the proposed model, this previously described conventional model, which utilizes one coordinate point to express emotions, is also evaluated for comparison.…”
Section: B Russell's Circumplex Model Of Affectmentioning
confidence: 99%
See 1 more Smart Citation
“…1), which has previously been used to facilitate human-robot interactions. Moreover, an earlier report suggests that an screen agent that uses Russell's circumplex model of affect can prompt more effective interactions with humans as compared with an agent using a conventional model [6]. In this study, the pleasure-displeasure and arousing-sleep axes correspond to a student's number of correct answers and their answer times, respectively.…”
Section: A Russell's Circumplex Model Of Affectmentioning
confidence: 83%
“…This model has proven beneficial for sustained interest in agent-human interactions. It has been reported that screen agents using this model facilitate more effective interactions with humans than do those that only express random emotions [6]. Moreover, it has been shown that a screen agent expressing positive emotions achieves more effective collaborative learning than does a screen agent expressing either negative or no emotions [7].…”
Section: Introductionmentioning
confidence: 99%